The potential of physical means for the manipulation of yam tuber dormancy - Barker, D.J.; Keatinge, J.D.H.; Asiedu, Robert (1999)
A range of physical means of manipulating yam tuber dormancy was tested, including the use of temperature, water, electric shock, microwave, heat and storage treatments. Most treatments had very little practical effect on tuber dormancy though differences in dormancy length between clones were detected. The complex mechanisms controlling dormancy are discussed and recommendations are made for further research.